Ownership on Islamic Economic Perspective and Director Ownership on Sharia Companies with Moderation Roles of Independent Commissioners - Noval, Muhammad; Raharjanti, Rani; Ali, Musab A. M. (IKONOMIKA, 2020)
This research aims to examine the ownership on Islamic economic and the ownership stock effect on firm performance and the moderating influence of independent commissioner on the connection between ownership stock and firm performance. Indicator of ownership stock studied was the ownership stock of the president director in the company. The firm performance studied by the calculation of Price per Earning Ratio. Then, the intended independent commissioners are the percentage of independent commissioners who are on the company's board of commissioners.This research uses qualitaitive method based on Islamic economic literature and quantitative methods basedon secondary data. Secondary data in this research are the financial report from firms that take the floor on Indonesia Stock Exchange (IDX). This investigation uses a population that is listed firms on Indonesian Sharia Stock Index (ISSI). Subsequently, the sample is filtered using purposive sampling techniques with the criteria of listed firms on Indonesia Stock Exchange and has the data needed in this investigation. As a result, the samples obtained were 296 companies. This research uses regression analysis with individual parameter significant test (t-test).Hypothesis testing results indicate that Sharia company ownershipis in accordance with Islamic economic perspective studies, and ownership stock with the indicator of ownership of the president director has an impact on firm performance with Price per Earning Ratio’s indicator, and independent commissioners based on the proportion of independent commissioners on the board of commissioners moderate the correlation between ownership stock and firm performance. Keywords: Ownership Stock, Firm Performance, and Independent Commissioners.